Flooding tolerance of four floodplain meadow species depends on age - Gattringer, Johannes P.; Donath, Tobias W.; Eckstein, R. Lutz; Ludewig, Kristin; Otte, Annette; Harvolk-Schöning, Sarah; Justus Liebig University Giessen (My University, 2017)
Numerous restoration campaigns focused on re-establishing species-rich floodplain meadows of Central Europe, whose species composition is essentially controlled by regular flooding. Climate change predictions expect strong alterations on the discharge regime of Europe s large rivers with little-known consequences on floodplain meadow plants. In this study, we aim to determine the effects of flooding on seedlings of different ages of four typical flood meadow species. To this end, we flooded seedlings of two familial pairs of flood meadow species of wetter and dryer microhabitats for 2 weeks each, starting 2, 4, 6, and 8 weeks after seedling germination, respectively. We show that a 2-week-flooding treatment had a negative effect on performance of seedlings younger than 6 weeks. Summer floods with high floodwater temperatures may have especially detrimental effects on seedlings, which is corroborated by previous findings. As expected, the plants from wet floodplain meadow microhabitats coped better with the flooding treatment than those from dryer microhabitats. In conclusion, our results suggest that restoration measures may perform more successfully if seedlings of restored species are older than the critical age of about 6 weeks before a spring flooding begins. Seasonal flow patterns may influence vegetation dynamics of floodplain meadows and should, therefore, be taken into account when timing future restoration campaigns.
Keywords: ddc:630